Engineered botulinum neurotoxin B with improved binding to human receptors has enhanced efficacy in preclinical models - Elliott, Mark (Sci Adv, 2019)
Although botulinum neurotoxin serotype A (BoNT/A) products are common treatments for various disorders, there is only one commercial BoNT/B product, whose low potency, likely stemming from low affinity toward its human receptor synaptotagmin 2 (hSyt2), has limited its therapeutic usefulness. We express and characterize two full-length recombinant BoNT/B1 proteins containing designed mutations E1191M/S1199Y (rBoNT/B1(MY)) and E1191Q/S1199W (rBoNT/B1(QW)) that enhance binding to hSyt2. In preclinical models including human-induced pluripotent stem cell neurons and a humanized transgenic mouse, this increased hSyt2 affinity results in high potency, comparable to that of BoNT/A. Last, we solve the cocrystal structure of rBoNT/B1(MY) in complex with peptides of hSyt2 and its homolog hSyt1. We demonstrate that neuronal surface receptor binding limits the clinical efficacy of unmodified BoNT/B and that modified BoNT/B proteins have promising clinical potential.